Normative providing of process of control of under travelling crane the ways of travelling cranes - Павлова, Ганна Олексіївна; Чернишенко, Олександр В’ячеславович; Лагода, Анна Миколаївна (Eastern-European Journal of Enterprise Technologies, 2012)
The method of control of rightness of location of claotype ways of travelling cranes is offered by a device with the use of laser ray, which allows to determine deviation of claotype way from nominal